2003
DOI: 10.1177/014556130308200821
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Complications following Tonsillectomy/UPPP: Is Step-Down Monitoring Necessary?

Abstract: We conducted a study to determine if the risk of airway compromise following tonsill ectomy with uvulopalatopharyn goplasty ju stifies the added cost and inconvenience of step-down monitoring in an intensive care unit. We perform ed a retrospective chart review of 130 patients with obstructive sleep apnea who had undergone isolated tonsillectomy with uvulopalatopharyngoplasty at our tertiary care center. The average length ofstay in the step-down unit was 18 hours. Wefound that only eight ofthese pati ents (6.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 7 publications
1
23
0
Order By: Relevance
“…The identified data showed much lower complication rates, ranging from 4% to 5.5% 11–14. The airway complication rate ranged from 0% to 1.4%, and there were no deaths 11, 13. General findings included that complications were higher with multiple simultaneous procedures, for example, multiple nasal procedures performed simultaneously with uvulopalatopharyngoplasty.…”
Section: Discussionmentioning
confidence: 93%
“…The identified data showed much lower complication rates, ranging from 4% to 5.5% 11–14. The airway complication rate ranged from 0% to 1.4%, and there were no deaths 11, 13. General findings included that complications were higher with multiple simultaneous procedures, for example, multiple nasal procedures performed simultaneously with uvulopalatopharyngoplasty.…”
Section: Discussionmentioning
confidence: 93%
“…Accordingly, these exclusions may have reduced the strength of the relation between OSAS severity and complications. In another retrospective study, 3 the preoperative OSAS severity of those with complications was not found to be significantly different from the preoperative OSAS severity of the entire study group. Oxygen supplementation was also given to all patients in the present study, which may have caused an underestimation of oxygenation related complications.…”
Section: Discussionmentioning
confidence: 81%
“…The most common complications during the immediate postoperative period are respiratory complications, including airway obstruction and hypoxemia and surgery‐related complications such as bleeding 2 . Several studies have been performed on the perioperative management of these patients, but studies on perioperative risk factor assessment are rare 3–5 . One retrospective study suggested that perioperative complications are related to the severity of OSAS, 4 but other authors found no correlation between complication rate and apnea severity 3,5 .…”
Section: Introductionmentioning
confidence: 99%
“…Multiple retrospective patient reviews have been conducted by various authors in an attempt to ascertain the complication rate after OSA surgery. The identified data showed much lower complication rates, ranging from 4% to 5.5% 11–14. The airway complication rate ranged from 0% to 1.4%, and there were no deaths 11, 13.…”
Section: Discussionmentioning
confidence: 87%